At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

helpppppppppppppppppp​

Helpppppppppppppppppp class=

Sagot :

Answer:

0

Step-by-step explanation:

(2m)/(2m+3)-(2m)/(2m-3)=1

Simplifying the left hand first

(2m)/(2m+3)-(2m)/(2m-3) = {2m(2m-3) - 2m(2m+3)}/(4m²-9)

(4m²-6m-4m²-6m)/(4m²-9) = (-12m) / (4m²-9)

Now this equates to 1

(-12m) / (4m²-9) = 1

-12m =  4m²-9

4m²+ 12m -9 =0 ⇒⇒⇒ This is a quadratic equation that has 2 real solutions.

4m²+ 12m -9 =0

m² + 3m + (3/2)²= 9/4 + 9/4

(m + 3/2)² = 18/4

m = √18/2 - 3/2 or m = -√18/2 - 3/ = 0.621 = -3.621

So we can say that the equation has NO extraneous solutions.

Answer = 0

(I'm pretty sure it's correct)